Lignin Modification Supported by DFT-Based Theoretical Study as a Way to Produce Competitive Natural Antioxidants - Lauberte, Liga; Fabre, Gabin; Ponomarenko, Jevgenija; Dizhbite, Tatiana; Evtuguin, Dmitry V; Telysheva, Galina; Trouillas, Patrick (Molecules (Basel, Switzerland), 2019)
The valorization of lignins as renewable aromatic feedstock is of utmost importance in terms of the use of sustainable resources. This study provides a deductive approach towards market-oriented lignin-derived antioxidants by ascertaining the direct effect of different structural features of lignin on the reactivity of its phenolic OH groups in the radical scavenging reactions. The antioxidant activity of a series of compounds, modeling lignin structural units, was experimentally characterized and rationalized, using thermodynamic descriptors. The calculated O-H bond dissociation enthalpies (BDE) of characteristic lignin subunits were used to predict the modification pathways of technical lignins. The last ones were isolated by soda delignification from different biomass sources and their oligomeric fractions were studied as a raw material for modification and production of optimized antioxidants. These were characterized in terms of chemical structure, molecular weight distribution, content of the functional groups, and the antioxidant activity. The developed approach for the targeted modification of lignins allowed the products competitive with two commercial synthetic phenolic antioxidants in both free radical scavenging and stabilization of thermooxidative destruction of polyurethane films.
Keywords: lignin; Temperature; Polyurethanes; Hydrogen; dimerizace; Electrons; lignins; teplota; teorie funkcionálu hustoty; Dimerization; Antioxidants; stabilizers for polymers; polyfenoly; Lignin; antioxidancia; Kinetics; spektroskopie infračervená s Fourierovou transformací; Polyphenols; protonová magnetická rezonanční spektroskopie; Density Functional Theory; teoretické modely; polyurethany; Spectroscopy, Fourier Transform Infrared; antioxidant activity; molecular rationalization; vodík; modification; Models, Theoretical; Proton Magnetic Resonance Spectroscopy; elektrony; kinetika